2022
DOI: 10.3390/molecules27185832
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma Suppressed MM In Vivo Engraftment by Increasing ROS and Inhibiting the Notch Signaling Pathway

Abstract: Multiple myeloma (MM) is the second most common hematologic malignancy. MM stem cells (MMSCs) are thought to be the main causes of in vivo engraftment and eventual recurrence. As a notable new technology, cold atmospheric plasmas (CAPs) show a promising anti-tumor effect, due to their production of various ROS. In this study, we found that different types of plasma could inhibit MM’s ability to form cell colonies, suppress MM in vivo engraftment, and extend survival times. We demonstrated that NAC (a ROS scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…In addition, ROS could also trigger oxidative stress to promote cell death [44]. Studies had con rmed that LTP can inhibit multiple myeloma and prolong survival time by inducing ROS production and inhibiting Notch signaling pathway [45]. In this experiment, it was found that the active oxygen content increased with the treatment time, but the cell viability decreased, which was consistent with the previous study.…”
Section: Kegg Pathway Enrichment Analysis Of Degssupporting
confidence: 90%
“…In addition, ROS could also trigger oxidative stress to promote cell death [44]. Studies had con rmed that LTP can inhibit multiple myeloma and prolong survival time by inducing ROS production and inhibiting Notch signaling pathway [45]. In this experiment, it was found that the active oxygen content increased with the treatment time, but the cell viability decreased, which was consistent with the previous study.…”
Section: Kegg Pathway Enrichment Analysis Of Degssupporting
confidence: 90%
“…Thiyagarajan et al, 2013; 2021 Plasma jet, Air Xu et al, 2019b Plasma jet, Argon Ji et al, 2020; Guo et al, 2021; Guo et al, 2022 Multiple myeloma Plasma jet, HeliumXu et al, 2016Xu et al, , 2018aXu et al, , 2018bXu et al, , 2019aQi et al, 2022b …”
mentioning
confidence: 99%